C1-Inhibitor protects from focal brain trauma in a cortical cryolesion mice model by reducing thrombo-inflammation - Albert-Weissenberger, Christiane; Mencl, Stine; Schuhmann, Michael K.; Salur, Irmak; Göb, Eva; Langhauser, Friederike; Hopp, Sarah; Hennig, Nelli; Meuth, Sven G.; Nolte, Marc W.; Sirén, Anna-Leena; Kleinschnitz, Christoph (Frontiers in Cellular Neuroscience, 2014)
Traumatic brain injury (TBI) induces a strong inflammatory response which includes blood-brain barrier damage, edema formation and infiltration of different immune cell subsets. More recently, microvascular thrombosis has been identified as another pathophysiological feature of TBI. The contact-kinin system represents an interface between inflammatory and thrombotic circuits and is activated in different neurological diseases. C1-Inhibitor counteracts activation of the contact-kinin system at multiple levels. We investigated the therapeutic potential of C1-Inhibitor in a model of TBI. Male and female C57BL/6 mice were subjected to cortical cryolesion and treated with C1-Inhibitor after 1 hour. Lesion volumes were assessed between day 1 and day 5 and blood-brain barrier damage, thrombus formation as well as the local inflammatory response were determined post TBI. Treatment of male mice with 15.0 IU C1-Inhibitor, but not 7.5 IU, 1 hour after cryolesion reduced lesion volumes by ~75% on day 1. This protective effect was preserved in female mice and at later stages of trauma. Mechanistically, C1-Inhibitor stabilized the blood-brain barrier and decreased the invasion of immune cells into the brain parenchyma. Moreover, C1-Inhibitor had strong antithrombotic effects. C1-Inhibitor represents a multifaceted antiinflammatory and antithrombotic compound that prevents traumatic neurodegeneration in clinically meaningful settings.